Multi-management schemes for MAF platforms - Lopes, Rui Pedro (2010)
Due to the crescent complexity of networks and systems, network management solutions are being pushed towards more distributed and cooperative models. Several specifications promoted by the IETF DISMAN charter already allow strong distribution of management tasks. Unfortunately, they are not adequate to achieve cooperative models. According to recent research, mobile agents provide a good platform to back cooperative models but several lacks are still identified - interoperability between different platforms and SNMP integration. Based on Mobile Agent Facility specification from the OMG, we propose a MIB to better integrate mobile agent models into SNMP frameworks and a GUI tool to monitor and control mobile agents platforms.